Proyecto de rehabilitación arquitectónica patrimonial caso de estudio Convento de la parroquia Santiago - Quito Benítez, Marjorie Fernanda (2018)
Abstract:The patrimonial rehabilitation means to improve the conditions of habitat by means of the improvements of the constructed medium, recovering the functions performed in the property that was declared well patrimonial in the 2008 by the INPC, by means of the Intervention in the Convent of the rural parish Santiago; this work was developed by making a stratigraphic analysis, constructive and pathological, proposing a sign for the diagnosis of the architectural elements, the evaluation of injuries of the property, the determination of interventions and actions that It requires this building, the architectural, functional and constructive proposal, since with the maintenance of the spatiality that characterized the Franciscan doctrine that around the cloister, were carried out activities of distribution and articulation of Spaces thus recovering its principal use and the incorporation of a program of lodging, green areas, recreational, of fishing for its current use.